Policies and measures implemented to reduce the impact of international sanctions on Iran's pharmaceutical sector - Farideh Emami; Abdol Majid Cheraghali (Wolters Kluwer Medknow Publications, 2022)
Background and purpose: Continuous evaluation of the policies and interventions could explore their efficacies in improving the accessibility and availability of medicines in the local market. This study explained the health system policies of the Islamic Republic of Iran concerning the impact of the economic sanctions on the local pharmaceutical market and addressed the issue of whether these policies were able to improve patients' access to medicines. Experimental approach: In this study, qualitative and quantitative research methods were used. In the qualitative part, semi-structured interviews with pharmaceutical system experts were used. In the next step, the structural analysis method was used. In the quantitative part, numerical sales data of the selected medicines were extracted and analyzed. Findings/Results: Reported statistics regarding the presence of the medicines in the market indicates the obvious fluctuations in the numerical sales of medicines in the studied years. This may indicate that the policies implemented are not able to fully compensate for the negative effects of sanctions and improve access to medicine. In addition, according to some experts, policy, and management weaknesses are mainly rooted in unresolved domestic hurdles which have exacerbated the effects of international sanctions on the country's pharmaceutical market. Conclusions and implications: Effective policy-making in response to economic sanctions can reduce the negative effect of international sanctions and result in drug shortages. Results of this study showed despite efforts made by the Iran health sector to subside the impact of sanctions on the pharmaceutical sector, there is an obvious disruption of the medicine supply chain in the market.